Water and Nutrition: Harmonizing actions for the United Nations Decade of Action on Nutrition and the United Nations Water Action Decade - Ringler, Claudia; Dias, Paulo (United Nations Systems Standing Committee on Nutrition, 2020)
This paper reviews these challenges as part of a broader analysis of the complex web of pathways that link water, food security and nutrition outcomes. Climate change and the growing demand for water resources are also considered, given their central role in shaping future water and nutrition security. The main conclusions are presented as three recommendations focused on potential avenues to deal with the complexity of the water-nutrition nexus, and to optimize outcomes. The analysis and recommendations in this report are geared toward both United Nations actors and other stakeholders with access to entry points to accelerate progress. Expanding collaboration and evidence generation is particularly important outside the WASH sector where some linkages have already been developed. This will be imperative for reducing trade-offs, and for strengthening momentum.